1994
DOI: 10.1093/jac/33.4.795
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics and safety of ciprofloxacin 400 mg iv thrice daily versus 750 mg po twice daily

Abstract: Comparative pharmacokinetics of i.v. and oral ciprofloxacin was studied in 24 healthy male subjects given 400 mg i.v. tds or 750 mg po bd in a randomized, double-blind, placebo controlled, crossover fashion with at least a 10 day washout period. Blood and urine samples were obtained following the first (single dose) and last (steady state) dose in each treatment period. After single dosing and under steady state conditions, the calculated 24 h area under the serum concentration versus time curve, (AUC0-24) aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 0 publications
1
22
0
2
Order By: Relevance
“…Drug, diluent, and elimination pumps of the in vitro system were set at appropriate rates to simulate a ciprofloxacin elimination half-life of 4 h based on pharmacokinetics in adults with normal renal function (10,51,52). Growth control experiments for each strain were conducted over 36 h at the same pump rates used for ciprofloxacin dosage regimen simulations.…”
Section: Methodsmentioning
confidence: 99%
“…Drug, diluent, and elimination pumps of the in vitro system were set at appropriate rates to simulate a ciprofloxacin elimination half-life of 4 h based on pharmacokinetics in adults with normal renal function (10,51,52). Growth control experiments for each strain were conducted over 36 h at the same pump rates used for ciprofloxacin dosage regimen simulations.…”
Section: Methodsmentioning
confidence: 99%
“…5 Group A was treated with 30 mg/kg/day of ciprofloxacin given orally every 12 hours (up to a maximum daily dose of 1,500 mg) in combination with 30 mg/kg/day of amoxycillin/ clavulanate, every 8 hours (up to a maximum daily dose of 1,500 mg), also given orally, plus an intravenous placebo.…”
Section: Definitionsmentioning
confidence: 99%
“…More recently, many researchers have demonstrated that febrile neutropenic patients comprise a heterogeneous group and may have several different levels of risk for complications related to the oncologic treatment. 1 In the last few years, several studies have tried to identify clinical and laboratory factors that make it possible to detect, in a heterogeneous group of neutropenic patients, Oral vs. intravenous empirical antimicrobial therapy in febrile neutropenic patients receiving childhood cancer chemotherapy Ângela Rech Cagol, 1 Cláudio Galvão de Castro Junior, 2 Maria Cristina Martins, 3 Adão Leal Machado, 4 Renato Chagas Ribeiro, 5 Lauro J. Gregianin, 6 Algemir Lunardi Brunetto 7 There is increasing evidence supporting the idea that neutropenic patients at low risk do not necessarily need long-term hospitalization and broad-spectrum antibiotic therapy for invasive bacterial infections. The strategies for this group include short-term antimicrobial treatments with consequent reduction of the length of hospital stay and outpatient management by means of oral antibiotics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os autores escolheram ciprofloxacina e amoxicilina/clavulanato como regime oral, porque ambos agentes são bem absorvidos quando ingeridos por via oral e porque essa associação apresenta boa cobertura contra bacilos gram-negativos e cocos gram-positivos 5 . Num conjunto de pacientes hospitalizados, comparou-se a eficácia da terapêutica oral versus cefepime, que se mostra como uma das opções de monoterapia endovenosa utilizada em pacientes com neutropenia febril.…”
Section: Introductionunclassified